2020
DOI: 10.1108/ijefm-03-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Shaping our perception of reality: sustainability communication by Canadian festivals

Abstract: PurposeThe purpose of this paper is to determine the extent of online communication by festivals regarding their sustainability practices using Cultivation Theory as the framework to determine perceived value creation.Design/methodology/approachA mixed method approach was utilized to achieve data triangulation through a content analysis of websites, content analysis of social media sites as well as interviews.FindingsFindings indicated that 64% of festivals did not communicate any sustainable practices through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Therefore, reputation orientation has implications for stakeholder satisfaction, socially responsible behaviour, ethical decision making, and sustainability. Dodds, Novotny and Harper (2020) recently sought to determine the extent of online communication by festivals regarding their sustainability practices has enabled the shaping of perceptions of reality. The study employed a mixed-method approach and the findings indicated that best practice festivals -having communicated 5.47 initiatives or more -were found to have been significantly more likely than non-best practice festivals to be music festivals and have been in operation longer.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, reputation orientation has implications for stakeholder satisfaction, socially responsible behaviour, ethical decision making, and sustainability. Dodds, Novotny and Harper (2020) recently sought to determine the extent of online communication by festivals regarding their sustainability practices has enabled the shaping of perceptions of reality. The study employed a mixed-method approach and the findings indicated that best practice festivals -having communicated 5.47 initiatives or more -were found to have been significantly more likely than non-best practice festivals to be music festivals and have been in operation longer.…”
Section: Resultsmentioning
confidence: 99%
“…The results reflect that the agents' perceptions of the impact that COVID-19 will have on the festival are negative. The perception of a lack of information and communication (Dodds et al , 2020) is noteworthy, causing high levels of uncertainty among the agents. The perception of the impacts on the industry is related to the reduction in employment and economic activity generated.…”
Section: Discussionmentioning
confidence: 99%
“…However, sustainability seems not to be a priority of music festivals. Dodds et al ( 2020 ) found that 64% of Canadian music festivals included in their sample did not communicate about their sustainability practices. Moreover, only 6% of them concentrated their sustainability campaign on social media, even though the literature shows that active communication is critical for developing and maintaining good relationships with participants (Luonila and Kinnunen 2019 ).…”
Section: Content Analysismentioning
confidence: 99%